2016
DOI: 10.1530/eje-16-0288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid autoimmunity and dysfunction in women with iron deficiency during early pregnancy: is it altered?

Abstract: Objective: Thyroid disorders and iron deficiency (ID) are associated with obstetrical and fetal complications. Iron is essential for the normal functioning of thyroid peroxidase (TPO-abs) and ID is frequent during pregnancy. The aim of this study was to compare the prevalence of thyroid autoimmunity (TAI) and dysfunction during the first trimester of pregnancy in women with and without ID. Design: Cross-sectional data analysis of 1900 pregnant women nested within an ongoing prospective collection of pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 42 publications
6
46
0
Order By: Relevance
“…In most studies in pregnant women, age > 30 years was not associated with increased serum TSH levels [9, 10, 38, 39] or TAI [39, 40]. In contrast, in the study by Veltri et al [40] serum TSH was significantly lower in women > 30 years, and, in a study by Korevaar et al [9], serum FT4 levels were significantly lower. Differences in serum TSH levels observed between studies may be explained by a different iodine and BMI status of the women.…”
Section: Established Variables Contributing To Variation In Thyroid Fmentioning
confidence: 96%
See 2 more Smart Citations
“…In most studies in pregnant women, age > 30 years was not associated with increased serum TSH levels [9, 10, 38, 39] or TAI [39, 40]. In contrast, in the study by Veltri et al [40] serum TSH was significantly lower in women > 30 years, and, in a study by Korevaar et al [9], serum FT4 levels were significantly lower. Differences in serum TSH levels observed between studies may be explained by a different iodine and BMI status of the women.…”
Section: Established Variables Contributing To Variation In Thyroid Fmentioning
confidence: 96%
“…In both studies, TAI was not taken into account or an exclusion criterion. In a recent study by Veltri et al [40] in 1,900 pregnant women performed in Belgium (mild ID), TAI was also analyzed in relation to Fe-D. In the Fe-D group (all over 35%), the prevalence of TAI and SCH was higher than in the non-Fe-D group (10 vs. 6 and 20 vs. 16%, respectively; p = 0.011 and 0.049, respectively).…”
Section: New Candidate Variables Contributing To Variation In Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu X et al found that serum TSH levels were negatively correlated with total body iron (TBI) levels at 4 to 12 weeks of gestation [18]. Flora Veltri et al found iron deficiency was frequent during the first trimester of pregnancy and was associated with a higher prevalence of thyroid autoimmunity, higher serum TSH and lower FT4 levels [25]. Because the prevalence of low body iron was substantially increased in pregnant women in the second trimesters than in the first trimesters (14.3 ± 2.1% vs. 6.9 ± 2.2%) [21], we investigated pregnant women from 13 to 24 weeks of gestation in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, a better thyroid function is found when iron stores are sufficient. In 2016 Veltri et al [64] described a similar situation, i.e. increased levels of TSH in conditions of iron deficiency.…”
Section: Magnesium and Iron In A Systems Approach Related To Thyroid mentioning
confidence: 94%